Design of Medicine Dispenser Vending Machine using Proteus Software (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
The rapid growth of healthcare demands efficient and automated solutions to improve medicine accessibility and reduce human dependency in dispensing systems. This paper presents the design and simulation of an automated medicine dispenser vending machine developed using Proteus Design Suite. The proposed system integrates a microcontroller-based control unit, keypad interface, display module, and motor-driven dispensing mechanism to ensure accurate and controlled delivery of prescribed medications.The system is designed to operate based on user authentication through an ID input method, enabling secure access to pre-assigned medicines. Once authenticated, the user can select the required medicine within predefined limits, and the system dispenses the medication while simultaneously updating inventory data. The simulation environment in Proteus allows real-time testing of circuit behavior, component interaction, and system reliability without physical implementation.The proposed design eliminates manual errors, reduces waiting time in pharmacies, and enhances patient convenience, especially in high-demand environments such as hospitals and clinics. Furthermore, the modular architecture enables easy scalability and future integration with advanced technologies such as IoT-based monitoring and cloud-based prescription management systems. The results demonstrate that the system is cost-effective, reliable, and suitable for modern healthcare automation.
Keywords: Automated Medicine Dispenser; Vending Machine System, Proteus Design Suite Simulation; Microcontroller-Based Design; Healthcare Automation; Healthcare AutomationEmbedded Systems, Inventory Management; Smart Healthcare System; Digital Prescription Handling